Pemberdayaan Masyarakat Dalam Efektifitas Kegiatan Senam Lansia Pada Lansia Terhadap Penurunan Tekanan Darah di Desa Sari Laba Biru Biru Kabupaten Deli Serdang Tahun 2022 - Desi Anggraini; Nurdiana Manurung (Journal of Community Development, 2022)
Aging is a lifelong process, not only starting at a certain time, but starting from the beginning of life. Growing old is a natural process, which means that a person has started the three stages of his life. from many studies and epidemiology, it is found that with increasing age and blood pressure rises, hypertension becomes a problem in the elderly because it is often found and becomes a major factor in heart failure and coronary heart disease. Especially for the elderly, the exercise used is elderly exercise. Elderly exercise can prevent functional loss of organs and can also reduce the risk of various diseases such as hypertension, diabetes mellitus, and coronary artery disease. Elderly exercise is also very important for the elderly to maintain their health. Elderly gymnastics is a sport that is light, easy to do and not burdensome for the elderly. Elderly gymnastics done regularly can reduce high blood pressure. This is because physical activity will reduce body fat, which is associated with high blood pressure. Especially for the elderly, the exercise used is elderly gymnastics.